GM foods and syariah principles: with special reference to GM wheat and soy / Siti Nor Syahidah Ismail, Azfahanim Rajaluddin and Fadzlin Mohd Yunos - Ismail, Siti Nor Syahidah; Rajaluddin, Azfahanim; Mohd Yunos, Fadzlin (2008)
Genetically Modified Foods (wheat and soy) are widely spread in this world. It is a technology that invented by the United States for the purpose of enhancing crops resistance to pesticides. Though there are many benefits claimed by the manufacturer of these foods, however, from this research, the disadvantages outweigh the benefits. Researches carried out by scientists warned that GM foods could cause serious damage to health and environment. GM ingredients introduced into many processed foods without informing consumers. These had caused unawareness among the customers on what they bought and make them doubtful on what they consumed as involves transfer of genes from unknown substance that may includes pork. Muslims consumers especially had seriously been affected by this biotechnology in foods era because; they are subjected to certain restrictions and prohibitions imposed by the Syariah concerning foods as only halal and good things can be consumed. Consumer rights against manufacturers or agent who failed to comply with requirement provided under Biosafety Act 2007 however very limited. Their right only arises when manufacturer or agent fails to comply with labelling but most manufacturers of do not labelled their products. This makes consumer rights to information denied by manufacturer whilst no action can be taken against manufacturers. Recommendation as imposing moratorium on GM wheat and soy, increase the number of experts in science also Islamic Princples also widened the parameter of Biosafety Act 2007 are several suggestions made to address issues of GM wheat and soy.